CAPE - A link amid thermodynamics and microphysics for the occurrence of severe thunderstorms - CHAUDHURI , SUTAPA; BHOWMICK, SUCHANDRA AICH (MAUSAM, 2006)
Lkkj & bl 'kks/k&i= dk mÌs’; dksydkrk ¼22°32¢] 88°20¢½ esa ekulwu iwoZ _rq ¼vizSy&ebZ½ ds nkSjku xtZ ds lkFk vkus okys Hkh"k.k rwQkuksa dh mRifÙk vkSj fodkl esa lgk;d es?k dh lw{e HkkSfrdh; izfØ;kvksa dh tk¡p djuk gSA bl v/;;u ls ;g irk pyk gS fd dksydkrk esa ekulwu&iwoZ _rq ds nkSjku xtZ ds lkFk vkus okys Hkh"k.k rwQkuksa ds nkSjku rkixfrdh;] xfrdh;] es?k dh lw{e HkkSfrdh vkSj fctyh pdeus dks J`a[kykc) djus esa laoguh; miyC/k foHko ÅtkZ ¼lh- ,- ih- bZ-½ lgk;d gSA bl v/;;u ls izkIr gq, ifj.kkeksa ls ;g irk pyk gS fd dksydkrk esa laoguh; miyC/k foHko ÅtkZ 1000 twYl izfr fd- xzk- ds Hkhrj izcy ikbZ xbZ tks eqDr laogu Lrj ¼,y- ,Q- lh-½ ls Åij fu/kkZfjr nkc Lrjksa ds Hkhrj ikbZ xbZ vkSj ok;q dh viMªk¶V xfr ds ln`’k eku fu"izHkkoh mRIykodrk Lrj ¼,y- ,u- ch-½ esa yxHkx 30 - 50 eh-@ lsdsaM ik, x,A bl v/;;u ls ;g Hkh irk pyk gS fd 5 fe- eh- rd ds O;kl ds vkdkj dh c¡wns fLFkj jg ldrh gS ftlds ckn vkdkj c<+us ds dkj.k cw¡nsa VwV tkrh gSaA tc cw¡n dh f=T;k 2-5 fe- eh- ls 3 fe- eh- dh ifjf/k esa gksrh gS rc cw¡nksa dk VwVuk 'kq: gks tkrk gS vkSj 3 fe- eh- ls 5 fe- eh- dh ifjf/k esa cw¡nksa ds VwVus dh laHkkouk vf/kd gksrh gS D;ksfd bl fLFkfr esa cw¡nksa ds yxkrkj VwVus dh dkj.k mudk thoudky cgqr NksVk gks tkrk gSA The aim of the present paper is to view the cloud microphysical processes entailed in the genesis and the development of the severe thunderstorms of pre-monsoon season (April - May) over Kolkata (22°32', 88°20'). The study shows that Convective Available Potential Energy (CAPE) is instrumental in establishing a linkage among thermodynamics, dynamics, cloud microphysics, and lightning during severe thunderstorm of pre monsoon season over Kolkata. The results of the present study reveal that for the thunderstorms reported over Kolkata, CAPE are found to be predominantly within 1000 joules per kgs within the prescribed pressure levels above the Level of Free Convection (LFC) and the corresponding values of the updraft speeds of the air are found to be nearly 30 - 50 m/s at the Level of Neutral Buoyancy (LNB). The study also depicts that the drops may grow up to the size of 5mm in diameter stably, beyond which, they tend to breakup due to the large drop instability. The breakup or splitting is observed to initiate when the drop radius is within the range of 2.5mm to 3mm and the breakup is most likely within the range of 3mm to 5mm because at this stage the lifetime of the drops are short due to the spontaneous breakup.